2006
DOI: 10.1091/mbc.e06-05-0388
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Kinetochore during Meiosis in Fission Yeast Schizosaccharomyces pombe

Abstract: During the transition from mitosis to meiosis, the kinetochore undergoes significant reorganization, switching from a bipolar to a monopolar orientation. To examine the centromere proteins that are involved in fundamental reorganization in meiosis, we observed the localization of 22 mitotic and 2 meiotic protein components of the kinetochore during meiosis in living cells of the fission yeast. We found that the 22 mitotic proteins can be classified into three groups: the Mis6-like group, the NMS (Ndc80-Mis12-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 50 publications
4
53
1
Order By: Relevance
“…Among them, only Cnp3 has been implicated in centromere function (51). Cnp3 is a centromere protein homologous to mammalian CENP-C and is required for chromosome segregation (52)(53)(54). Our ChIP-chip results showed that H2A.Z Pht1 is enriched at the promoter region of CENP-C Cnp3 , which was confirmed by PCR-based quantification (Fig.…”
Section: Both Msc1 and Swr1 Are Required For Proper Chromosome Segregsupporting
confidence: 72%
“…Among them, only Cnp3 has been implicated in centromere function (51). Cnp3 is a centromere protein homologous to mammalian CENP-C and is required for chromosome segregation (52)(53)(54). Our ChIP-chip results showed that H2A.Z Pht1 is enriched at the promoter region of CENP-C Cnp3 , which was confirmed by PCR-based quantification (Fig.…”
Section: Both Msc1 and Swr1 Are Required For Proper Chromosome Segregsupporting
confidence: 72%
“…The outer kinetochore complex was visualized by live analysis of meiotic cells harbouring an endogenously tagged functional allele of Dad1, a component of the DASH complex, which interacts directly with microtubules. In a wt background, Dad1 remains associated with the centromere throughout meiosis [28][29][30] (Supplementary Fig. 2).…”
Section: Failed Centromere Assembly Without Bouquetmentioning
confidence: 96%
“…To examine localization of additional factors at the base of the kinetochore, we assessed the cenI-TetO/R localization of endogenously tagged and functional Mis6, an essential Cnp1-loading factor 24 that remains on the centromere throughout meiosis in a wt setting 28 . The cenI-TetO/R signal remains unsegregated in 12.3% of bqt1∆ meiocytes, in line with the representation of one of the three fission yeast centromeres by cenI-TetO/R, and cenI-TetO/R fails to associate with visible Mis6-GFP in 88% of those cases ( Supplementary Fig.…”
Section: Failed Centromere Assembly Without Bouquetmentioning
confidence: 99%
“…Recent studies have revealed that a group of proteins disappear from the centromere during meiotic prophase, regulated by mating pheromone signaling [22,23]. In mitotic interphase, a number of proteins assemble at the centromere and connect the centromere to the SPB; when the cell enters mitosis, they form the kinetochore as an interface between the centromere and spindle microtubules.…”
Section: Centromeres Are Disassembled In Response To Mating Pheromonementioning
confidence: 99%